2019
DOI: 10.3390/ijms20174185
|View full text |Cite
|
Sign up to set email alerts
|

Role of NF-κB in Platelet Function

Abstract: Platelets are megakaryocyte-derived fragments lacking nuclei and prepped to maintain primary hemostasis by initiating blood clots on injured vascular endothelia. Pathologically, platelets undergo the same physiological processes of activation, secretion, and aggregation yet with such pronouncedness that they orchestrate and make headway the progression of atherothrombotic diseases not only through clot formation but also via forcing a pro-inflammatory state. Indeed, nuclear factor-κB (NF-κB) is largely implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 170 publications
(197 reference statements)
1
30
0
2
Order By: Relevance
“…In patients with CAD, circulating levels of chemerin also correlate with the severity of CAD [ 129 , 130 , 131 , 132 ]. Some studies carried out in HUVECs have shown that chemerin participates in endothelial inflammation by inducing nuclear factor-κB (NF-κB), which is a key player in vascular inflammation, atherosclerosis development, and its pathological complications in atherothrombotic diseases [ 133 , 134 ] and the monocyte–endothelial adhesion [ 135 ]. In human VSMCs, chemerin has pro-apoptotic, pro-inflammatory, and proliferative effects that are mediated by nicotinamide adenine dinucleotide phosphate oxidase (Nox) activation and redox-sensitive mitogen-activated protein kinases signalling [ 136 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…In patients with CAD, circulating levels of chemerin also correlate with the severity of CAD [ 129 , 130 , 131 , 132 ]. Some studies carried out in HUVECs have shown that chemerin participates in endothelial inflammation by inducing nuclear factor-κB (NF-κB), which is a key player in vascular inflammation, atherosclerosis development, and its pathological complications in atherothrombotic diseases [ 133 , 134 ] and the monocyte–endothelial adhesion [ 135 ]. In human VSMCs, chemerin has pro-apoptotic, pro-inflammatory, and proliferative effects that are mediated by nicotinamide adenine dinucleotide phosphate oxidase (Nox) activation and redox-sensitive mitogen-activated protein kinases signalling [ 136 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…CVDs are often caused by thrombotic events such as coronary heart disease. Platelets are major players in the occurrence of CVDs since they are involved in various thrombo-inflammatory diseases, particularly atherosclerosis and its progression to atherothrombosis in acute coronary syndrome (ACS) patients [ 1 ]. In fact, platelets control key hemostasis and formation of thrombosis, nevertheless, thrombosis can become pathological when it occurs, predominantly after the rupture of an atherosclerotic plaque.…”
Section: Introductionmentioning
confidence: 99%
“…Of the two subunits (IκBα and IκBβ), IκBα is the most represented. Upon activation, the IκB kinase (IKK) complex phosphorylates IκB causing its proteasome-mediated degradation, releasing NF-κB for nuclear translocation to exert its roles as a transcription factor for transcription of pro-inflammatory and pro-survival genes [ 1 ]. In such cellular settings, the role of NF-κB is genomic and well documented in nucleated cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the CD40L/CD40 complex induces activation of nuclear factor kappa B (NF-κB), which involves both IKK and IKB in the NF-κB signaling pathway. The latter exhibits a different non-genomic function in macrostemon platelets and induces inflammation and thrombosis ( Hachem et al, 2012 ; Karim et al, 2015 ; Paul et al, 2017 ; Xu et al, 2017 ; Kojok et al, 2019 ). In addition, the conjugation of TRAF protein (E3 ligase) with the CD40 receptor plays an important role in the CD40L/CD40 pathway, by mediating the activation of the canonical and non-canical NF-κB pathways as well as the MAPK pathway in response to CD40 ( Hadweh et al, 2014 ; de Jong et al, 2016 ; El Hokayem et al, 2017 ; Chen et al, 2018 ; Seijkens et al, 2018 ; Johansson et al, 2019 ; Unsworth et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%